Benign prostatic hyperplasia: A clinical review. Issue 8 (August 2016) - Skinder, Danielle; Zacharia, Ilana; Studin, Jillian; Covino, Jean
Abstract : ABSTRACT: Benign prostatic hyperplasia (BPH) is an increasingly common diagnosis seen in men over age 50 years. Primary care providers must be aware of patient presentation, diagnostic tests, appropriate lifestyle modifications, treatment options, and potential complications in order to properly manage and educate patients with BPH. If left untreated, BPH can significantly decrease a man's quality of life; however, many pharmacologic and surgical treatments are available to control the symptoms.